Case report: Filariasis presenting as an intra-abdominal cyst - Kapoor, Abhay K; Puri, Sunil Kumar; Arora, Ankur; Upreti, Lalendra; Puri, Amrender S (Indian Journal of Radiology and Imaging, 2011)
Filariasis is an endemic infection seen in the tropical and subtropical regions of the world, presenting with lymphatic dysfunction in the form of lymphocele, hydrocele, chyluria, or groin lymphadenovarix. We report a rare presentation of filariasis as an intra-abdominal cystic mass.
Keywords: Abdominal cyst; filaria; lymphadenovarix